Knowledge and perceptions of the profession of translators and interpreters among legal practitioners in Spain - Alcalde Peñalver, Elena; Pajares Nievas, José Sergio (Onomázein, 2019)
Although legal professionals may be fully aware of the regulations on the right to translation and interpreting, they tend to be less aware of the implications of legal and sworn translation and interpreting. It is therefore of the utmost importance to develop the current state of knowledge on translation and interpreting in legal contexts, in a way that will professionalise the image of translators and interpreters in these areas. After conducting previous research studies in which we analysed the combination of language and law in university curricula and another one in which we sought to raise awareness among law students about the importance of interdisciplinary work between linguists and legal experts (2017a), with this study we aimed to go further by conducting research on how much legal professionals know about translation and interpreting in Spain. After a preliminary literature review on the topic, we will explain the methodology of our study and then show the results of the survey that was distributed among legal professionals in Spain. The conclusions will allow us to critically reflect on the topic and suggest ways to go past the thick veil of ignorance that still covers the work carried out by professional translators and interpreters.